Proceso de atención nutricional en paciente masculino de 44 años de edad con accidente cerebro vascular. - León Platón, María Gabriela (2023)
This case study is based on a 44-year-old male patient with a cerebrovascular accident who presented a 2-day history of sudden-onset occipital headache, intensity 7/10, vertigo, dysphagia, and blurred vision. The objective of this clinical case was to carry out the nutritional care process in a 44-year-old male patient with a cerebrovascular accident, who went to the emergency center due to a clinical picture of 2 days of evolution characterized by sudden onset occipital headache of intensity 7 /10 with vertigo, dysphagia and blurred vision. Conscious and oriented in time and space, direct and consensual photomotor reflex preserved. The patient was assessed using the anthropometric method, resulting in 25.6 Kg/m2 of Body Mass Index (Overweight). A nutritional plan was prepared according to the needs and requirements of the patient of 1857 Kcal distributed as follows: CHO 57% Proteins 15% and Fats 38%. Nutritional follow-up was carried out and variation in body weight data was evidenced, which decreased their Body Mass Index and in the food anamnesis it was observed that an adequate food intake was being made.